Passing experiences on to future generations: endocrine disruptors and transgenerational inheritance of epimutations in brain and sperm. Issue 10 (2nd November 2018) - Gillette, Ross; Son, Min Ji; Ton, Lexi; Gore, Andrea C.; Crews, David
ABSTRACT: All animals have body burdens of polychlorinated biphenyls (PCBs) despite their ban decades ago. These and modern endocrine-disrupting chemicals (EDCs) such as the fungicide vinclozolin (VIN) perturb hormone signaling and lead to dysfunctions following prenatal exposures. Beyond direct exposures, transgenerational disease phenotypes can persist for multiple generations without subsequent exposure. The mechanisms of action of these EDCs differ: VIN is anti-androgenic while the PCB mixture Aroclor 1221 (A1221) is weakly estrogenic. Based on limited evidence for the inheritance of epimutations in germline, we measured DNA methylation in brain and sperm of rats. Pregnant dams were exposed from day 8–18 of gestation to low dosages of VIN, A1221, or the vehicle. To produce paternal lineages, exposed F1 males were bred with untreated females, creating the F2 and subsequently F3 generations. In adult F1 and F3 males, mature sperm was collected, and brain nuclei involved in anxiety and social behaviors (CA3 of the hippocampus; central amygdala) were selected for assays of epimutations in CpG islands using reduced representation bisulfite sequencing. In F1 sperm, VIN and PCBs induced differential methylation in 215 and 284 CpG islands, respectively, compared to vehicle. The majority of effects were associated with hypermethylation. Fewer epimutations were detected in the brain. A subset of differentially methylated regions were retained from the F1 to the F3 generation, suggesting a common mechanism of EDC and germline epigenome interaction. Thus, EDCs can cause heritable epimutations in the sperm that may embody the future phenotype of brain-behavior disorders caused by direct or transgenerational exposures.